Exit from communism (Transaction, 1993)
The book is an account of the revolutionary years 1989 to the present as experienced by those compelled to submit to communist rule. It is an account also of many in the West perceived these events, how it continues to views this world today, and why, despite the continued protests about all that the older and more stable democracies wish to do to assist those that are only now being created, these efforts have to date been so limited. This book is not only about those who have made their exit from communism, and what they have experience since, but also about those still dominated by communist elites, and those that never were. It treats the former Soviet Union, Russia, Yugoslavia, Czechosclovakia, and Poland.